Acute colonic pseudo-obstruction (ogilvie’s syndrome) or colonic perforation: A rare complication following cesarean section (Indian Journal of Case Reports, 2020)
Ogilvie’s syndrome or pseudo-obstruction of the colon shows up as a clinical picture of acute obstruction of the large bowel without an associated pathological lesion as usually occurs in older patients. Here, we report a case series of three cases of Ogilvie’s syndrome following caesarean section. The caesarean section seems to be the most common operative procedure associated with this syndrome. The diagnosis was made by plain X-ray of the patient’s abdomen, which revealed dilated gut loops or air under the diaphragm in case of perforation. The pathological cause seems to be the disturbance of the autonomic innervation of the colon. The colon should be decompressed rapidly using colonoscopy. Surgery should be reserved for cases that have complications or that have been refractory to conservative treatment. Of our three cases, one was treated successfully by colonoscopic decompression and IV neostigmine, whereas, rest two patients presented late with colonic perforation. So they were immediately taken for exploratory laparotomy.